Inhibitory interactions between spiking and nonspiking local interneurons in the locust - Burrows, M (J Neurosci, 1987)
Simultaneous intracellular recordings were made from pairs of spiking and nonspiking local interneurons in the metathoracic ganglion of the locust to search for interactions that might underlie tactile and proprioceptive reflexes of a leg. A spike in a spiking local interneuron is followed after a consistent latency (0.6 +/- 0.12 msec, mean +/- SD) by an IPSP in a particular nonspiking interneuron. The connection appears to be direct and chemically mediated. By contrast, manipulating the membrane potential of a nonspiking interneuron by injecting current through the recording electrode has no direct effect on a spiking local interneuron. The direct interactions between pairs of these local interneurons are thus one-way. If, however, the current injected into a nonspiking interneuron is sufficient to evoke a movement by exciting motor neurons, then the spiking interneuron can be excited or inhibited by the resulting reafference. The spiking local interneurons have excitatory regions in their receptive fields formed by arrays of exteroreceptors or by proprioceptors at specific joints. The inhibitory connections mean that the postsynaptic nonspiking interneurons have corresponding inhibitory regions to their receptive fields. Several spiking local interneurons with similar receptive fields may converge onto one nonspiking interneuron. Some nonspiking interneurons, however, have larger receptive fields than an individual spiking interneuron, again indicating convergence of inputs. The specificity of the inhibitory connections preserves the spatial representation of sensory information for use in particular reflexes. For example, touching hairs on the ventral femur evokes a reflex extension of the tibia. Spiking interneurons excited by these receptors inhibit a nonspiking interneuron that would cause the opposing and therefore unwanted flexion movement. Viewed in this behavioral context, the pattern of connections between the local interneurons forms the basis of the circuitry for the local reflex adjustments of posture and locomotion.